Metode Gamifikasi untuk Pembelajaran Menulis Cerpen Siswa Kelas XI SMK Islam Darussalam - Ramadhani, Abd Wafir; Wachidah, Liana Rochmatul (MARDIBASA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2024)
This article analyzes the application of gamification methods that are used as an effort to improve the short story writing skills of class XI students of SMK Islam Darussalam. Gamification is a learning method that involves game elements such as leaderboards, points, challenges, and prizes in learning, which are proven to be able to create interesting and interactive learning. This study uses a qualitative method with a case study approach. This approach is used because it allows researchers to gain a deep understanding of the phenomenon being studied in a real context. This study shows that the gamification method can improve students' writing skills, because its application can create active and enjoyable learning. The thing that must be considered in implementing this method is the right strategy, because with the right strategy gamification has the potential to create dynamic and student-centered learning, thus helping students improve their skills, especially short story writing skills.